IMF Survey : Volume 29, Issue 22. (IMF Survey; IMF Survey ;, 2000)
Following are edited excerpts from IMF Managing Director Horst Kohler's remarks, as prepared for delivery at the conference 'Completing Transition: The Main Challenges,' held in Vienna, Austria, on November 6. The full text is available on the IMF's website (www.imf.org).